2015
DOI: 10.1364/boe.6.003217
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of distortion in photothermal microscopy and its application to the high-resolution three-dimensional imaging of nonfluorescent tissues

Abstract: A scheme for reducing image distortion in photothermal microscopy is presented. In photothermal microscopy, the signal shape exhibits twin peaks corresponding to the focusing or defocusing of the probe beam when a sample is scanned in the axial direction. This causes a distortion when imaging a structured sample in the axial plane. Here, we demonstrate that image distortion caused by the twin peaks is effectively suppressed by providing a small offset between two the focal planes of the pump and the probe beam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…The wavelength of the pump beam overlapped the absorption spectrum of the gold nanoparticles due to the plasmon resonance peak at 524 nm. It has been also demonstrated that either of the twin peaks is suppressed by an offset between the focal planes of the pump and probe beams (Figure 4a) [35]. Figure 4b shows PT images of a 20 nm gold nanoparticle with a variety of ∆z.…”
Section: Improvement In the Spatial Resolutionmentioning
confidence: 86%
See 2 more Smart Citations
“…The wavelength of the pump beam overlapped the absorption spectrum of the gold nanoparticles due to the plasmon resonance peak at 524 nm. It has been also demonstrated that either of the twin peaks is suppressed by an offset between the focal planes of the pump and probe beams (Figure 4a) [35]. Figure 4b shows PT images of a 20 nm gold nanoparticle with a variety of ∆z.…”
Section: Improvement In the Spatial Resolutionmentioning
confidence: 86%
“…It has been also demonstrated that either of the twin peaks is suppressed by an offset between the focal planes of the pump and probe beams (Figure 4a) [35]. Figure 4b shows PT images of a 20 nm gold nanoparticle with a variety of z.…”
Section: Improvement In the Spatial Resolutionmentioning
confidence: 88%
See 1 more Smart Citation
“…Thus, it does not involve the distortion of mitochondria due to the labeling process. In addition, its advantages include simplification of sample preparation due to the absence of a requirement for labeling and its superior resolution (lateral, ~200 nm; depth, ~500 nm) achieved by the quadratic dependence of the point spread function in pump-probe configuration [18][19][20]. To date, PT imaging of mitochondria has been performed only in limited tissue types, including nematodes [17], HeLa cells [16,21], and kidney cells [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] The photothermal microscopy has been applied to various materials 6,7 including several biological samples such as cytochrome c in mitochondria, [8][9][10][11] hemoglobin in blood vessels, 12 and skin cancers. [13][14][15] Recently, our group reported a new photothermal microscope system with high detection sensitivity with low noise by a balance detection method [16][17][18] and with high-speed scanning utilizing a Galvano mirror. 19 Further resolution improvement of the pump-probe microscope applied to biological samples was achieved by non-linear detection scheme using a supercontinuum white light laser taking advantages of its high intensity with the piezo-driven stage system.…”
Section: Introductionmentioning
confidence: 99%